101 Online Classroom Strategies Training Playgroup Teachers to Improve Bonding: 101 Strategi Kelas Online Pelatihan Pada Guru Playgroup Untuk Meningkatkan Bonding - Arundaya, Thalita Salsabila Yumna; Prameswari, Anggita; Dwihastuty, Aprilia; Tobing, Xylona Pyriell Martua Lumban; Salsabila, Faridah Zahirah; Yuniar, Adiya Alifa; Rasyida, Afinnisa (Universitas Muhammadiyah Sidoarjo, 2024)
The rise of online teaching is currently being carried out due to a pandemic which results in everyone having to limit interactions, this is aimed at reducing transmission of the coronavirus. Likewise, the existence of online teaching has resulted in the teaching staff, especially playgroup teachers having difficulty making a bonding with their students. They feel limited space and interaction between teachers and students. The existence of this, the researcher conducted a training to increase bonding between teachers and students by providing training in the form of “101 Online Class Strategies” in this training there were 5 teachers involved in this activity. There are 4 female teacher’s and 1 male teacher with the mean pre-test 111.00 and post-test of 115.40. Keywords: Training, Playgroup, Bounding, Teacher, Pandemic